Bayesian statistics in luminescence dating: the ’baSAR’-model and its implementation in the R package ’Luminescence’ - Mercier, Norbert; Kreutzer, Sebastian; Christophe, Claire; Guérin, Guillaume; Guibert, Pierre; Lahaye, Christelle; Lanos, Philippe; Philippe, Anne; Tribolo, Chantal (Ancient TL, 2016)
A function named analyse baSAR() was written using the statistical programming language R and its code is now available within the R package ’Luminescence’. The function allows the application of the Bayesian hierarchical model ’baSAR’ proposed by Combes et al. (2015) and comes with additional features to analyse luminescence data in a straight forward way. Example scripts are provided showing the possible numerical and graphical outputs.
Gesehen am 26.03.2025